Thyroid Hormone Effects on Sensory Perception, Mental Speed, Neuronal Excitability and Ion Channel Regulation - Dietzel, Irmgard D.; Mohanasundaram, Sivaraj; Niederkinkhaus, Vanessa; Hoffmann, Gerd; Meyer, Jens W.; Reiners, Christoph; Blasl, Christiana; Bohr, Katharina (IntechOpen, 2012)
None